Emission of Brominated Pollutants from Waste Printed Circuit Boards during Thermal Treatment: A Review - Jun Wan; Jia Sun; Xiang-Lin Zhao; An-Sheng Le; Peng-Bo Ren; Ming-Xiu Zhan; Xiao-Qing Lin; Tong Chen (Aerosol and Air Quality Research)
Abstract With the improvements seen in electronic equipment in recent years, the amount of electronic waste generated has increased dramatically. Researchers must find a way to treat waste printed circuit boards (WPCBs) without harming the environment as soon as possible. The disposal of WPCBs generates many brominated pollutants, which have a great impact on human health and the surrounding environment. At present, research on the WPCB disposal process has mainly been focused on efficient resource recovery; studies of pollutant emission have been limited to chlorinated dioxins, and research on brominated pollutants is relatively limited. This paper summarizes and analyzes the brominated pollutants emitted during the recycling of waste circuit boards, summarizes the sources and paths for the generation of brominated pollutants, and describes a series of studies performed to determine the emission characteristics and impact factors for brominated pollutants. The effects of raw materials, temperature, atmosphere, and reaction time on the emission of brominated pollutants are discussed, as are three methods of controlling the pollutants. It was found that when the temperature was controlled at 850–1200°C, the reaction time was greater than 2 s, the air flow rate was 3–4.5 m s−1, and the excess air coefficient was 1–2, the impact of pollutant emissions was relatively small. It is hoped that this paper will provide help to other researchers and practitioners on WPCB recycling.